Proteomic Identification of Immune-Related Silkworm Proteins Involved in the Response to Bacterial Infection. Issue 4 (25th July 2019) - Chen, Shiyi; Dong, Zhaoming; Ren, Xiu; Zhao, Dongchao; Zhang, Yan; Tang, Muya; Han, Jiaxuan; Ye, Lin; Zhao, Ping
Abstract: Bombyx mori ( Lepidoptera: Bombycidae ) is an important economic insect and a classic Lepidopteran model system. Although immune-related genes have been identified at a genome-wide scale in the silkworm, proteins involved in immune defense of the silkworm have not been comprehensively characterized. In this study, two types of bacteria were injected into the silkworm larvae, Gram-negative Escherichia coli ( Enterobacteriales: Enterobacteriaceae), or Gram-positive Staphylococcus aureus ( Bacillales: Staphylococcaceae ). After injection, proteomic analyses of hemolymph were performed by liquid chromatography—tandem mass spectrometry. In total, 514 proteins were identified in the uninduced control group, 540 were identified in the E. coli- induced group, and 537 were identified in the S. aureus -induced group. Based on Uniprot annotations, 32 immunological recognition proteins, 28 immunological signaling proteins, and 21 immunological effector proteins were identified. We found that 127 proteins showed significant upregulation, including 10 immunological recognition proteins, 4 immunological signaling proteins, 11 immunological effector proteins, and 102 other proteins. Using real-time quantitative polymerase chain reaction in the fat body, we verified that immunological recognition proteins, signaling proteins, and effector proteins also showed significant increases at the transcriptional level after infection with E. coli and S. aureus . Five newly identified proteins showed upregulation at both protein and transcription levels after infection, including 30K protein, yellow-d protein, chemosensory protein, and two uncharacterized proteins. This study identified many new immune-related proteins, deepening our understanding of the immune defense system in B. mori . The data have been deposited to the iProX with identifier IPX0001337000.